Body composition of elite youth soccer players with respect to field position - Mala, L.; Maly, T.; Zahalka, F.; Hrasky, P. (Journal of Physical Education and Sport, 2015)
The aim of the study was to determine and compare selected body composition variables from the field position perspective in elite youth soccer players. The research sample consisted of three youth elite soccer teams of U19 category. Totally, 73 soccer players (age = 18.7 ± 0.3 years) were divided according to their field positions into: goalkeepers (n = 7), defenders (n = 24), midfielders (n = 31) and attackers (n = 11). Following parameters were observed: Lean body mass (LBM), percentage of Fat Mass (FM), Body Cell Mass (BCM) and Extra Cellular Mass (ECM) and their mutual ratio (ECM/BCM) as well as segmental proportion of muscle mass. Multilevel analysis of variance revealed significant differences in means of the selected parameters between the observed groups (field positions) (F(30.186) = 3.01, ë = 0.29, p < 0.01, ç2 = 0.33). Analysis of variance showed a significant effect of the following parameters: body mass F(3.73) = 6.29, p < 0.01, ç2 = 0.21, lean body mass: F(3.73) = 11.65, p < 0.01, ç2 = 0.34, segmental muscle mass distribution for right leg F(3.73) = 6.09, p < 0.01, ç2 = 0.21, left leg F(3.73) = 8.35, p < 0.01, ç2 = 0.27, right arm F(3.73) = 9.07, p < 0.01, ç2 = 0.28 and left arm F(3.73) = 8.11, p < 0.01, ç2 = 0.26. Goalkeepers significantly differed from defenders and midfielders in body weight and achieved significantly greater proportion in segmental distribution of muscle mass in all limbs in comparison to the other field positions. Research has shown differences between anthropometric indicators and body composition parameters in players on the basis of division according to their field positions.